Estudo dos aspectos demográficos da onça-parda (Puma concolor) na Estação Ecológica de Itirapina no estado de São Paulo por meio da análise de amostras não invasivas - Rodríguez, Karla Verónica Chávez (2013)
Landscape fragmentation and habitats loss caused by human activities have led to a decline cougar populations (Puma concolor). Delimiting populations and establish rates of migration between them is essential to understanding its dynamics and therefore planning conservation measures. The present study propose to use molecular techniques with noninvasive samples to evaluate the status of a population of P. concolor inhabiting in a patch of 32km2 of São Paulo State. The population size was of 6 individuals and its density ranged between 4.6 and 1.8/100km2. In addition, this population was analyzed together with other individuals of P. concolor collected in the northeast region of the state. Bayesian clustering methods were used to identify genetic populations, and Bayesian multilocus genotyping method to estimate migration rates, in order to determinate possible source-sink dynamics. Finally, two subpopulations separated by the highway SP-310 were identified. The results showed that the subpopulation located on the east of the highway behaved as source population and the another one found on west as a sink. Future researches of P. concolor populations must aim to determinate the populations structures and thereby facilitate the establishment of effective action plans for the conservation of the species.